Determinants of Political Trust. A Cross-Sectional Study - Morales Casetti, Marjorie; Bustos Gutiérrez, Marco; Silva Sánchez, Javiera (Revista del CLAD Reforma y Democracia, 2018)
Political trust has become a scarce commodity in today’s societies. Political science seeks for the factors that have an impact on political trust and to answer how is it possible to create it. This article estimates a multiple linear regression model considering information from 2015 for 62 countries. The results show that social trust and economic growth have positive and significant effects on political trust. Contrary to expectations, there were no significant effects of the quality of public services or the impartiality of the government on political trust. The challenge is to design policies that contribute to increase economic growth and social trust
Keywords: Political Context; Political Analysis; Economic Growth